Rhythmic prose in The Lord of the Rings by J.R.R. Tolkien - Vladimir A. Afanasev (RUDN Journal of Studies in Literature and Journalism)
Concerns rhythmic prose in The Lord of the Rings novel by J.R.R. Tolkien which, though extensively represented the novel, is seldom considered in most research papers. The novel contains over 70 poetic texts and should be viewed as a complex prosimetrum, as multifarious interconnections between prose and verse is an integral part of The Lord of the Rings poetics. The marginal manifestations of this mixed style, such as rhythmic prose, are of special concern. The recognition and further analysis of most non-occasional fragment of prose metre in the novel may be fully accomplished only with due regard to other Tolkien’s works (especially from the Legendarium) and the peculiarities of his style (both in poetry and in prose) in general. Considering three selected fragments of rhythmic prose, we aim to specify their connections with some songs and poems either from The Lord of the Rings itself, or outside the novel; the context and rhythmic pattern of another fragment develop possible allusions even to hypothetically existing texts within Tolkien’s literary world and poetic traditions of the people of Middle-earth. The variety of the representation of rhythmic prose in The Lord of the Rings is far from being limited to the mentioned categories, and further research is required.